2020
DOI: 10.1097/bpb.0000000000000609
|View full text |Cite
|
Sign up to set email alerts
|

Retained foreign objects in casts in children

Abstract: Cast immobilization is a noninvasive and effective option in the treatment of fractures in children. However, its use can be associated with complications, such as pressure sores, skin infections, thermal injuries, and joint stiffness. In clinical practice, retained foreign objects in casts are not uncommon. This study aims to ascertain reasons for foreign objects being retained in casts and their effects on the skin. Eighteen children with retained foreign objects in their casts were identified and interviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…3,4 In addition, as moisture retained within the cast causes itch, it was reported that pediatric patients often insert foreign objects in the cast, in an attempt to alleviate the itch. 5 The insertion of foreign objects such as stationary and coins could lead to complications such as pressure sores, skin infections, thermal injuries, and joint stiffness. 5,6 The exposure of nonwaterproof fiberglass cast to water resulting in a wet cast could also lead to skin maceration and breakdown.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…3,4 In addition, as moisture retained within the cast causes itch, it was reported that pediatric patients often insert foreign objects in the cast, in an attempt to alleviate the itch. 5 The insertion of foreign objects such as stationary and coins could lead to complications such as pressure sores, skin infections, thermal injuries, and joint stiffness. 5,6 The exposure of nonwaterproof fiberglass cast to water resulting in a wet cast could also lead to skin maceration and breakdown.…”
mentioning
confidence: 99%
“…5 The insertion of foreign objects such as stationary and coins could lead to complications such as pressure sores, skin infections, thermal injuries, and joint stiffness. 5,6 The exposure of nonwaterproof fiberglass cast to water resulting in a wet cast could also lead to skin maceration and breakdown. 6 The resulting damaged skin barrier could also facilitate the entry of bacteria and fungi leading to infections.…”
mentioning
confidence: 99%
See 2 more Smart Citations